1995
DOI: 10.1152/ajpheart.1995.269.1.h297
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cardiac Na(+)-K+ pump current: role of protein and nonprotein sulfhydryl redox status

Abstract: Oxidant stress alters protein structure and function, possibly through the modification of the redox status of regulatory protein sulfhydryl groups. We used the sulfhydryl-blocking reagent p-chloromercuriphenylsulfonic acid (pCMPSA), applied selectively and independently to either the intracellular or extracellular environment, to study the relationship between blocking protein sulfhydryl groups and Na(+)-K+ pump current (i.p.). In guinea pig ventricular myocytes voltage clamped at -30 mV, extracellular pCMPSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
1
17
1
Order By: Relevance
“…Protein thiols have been implicated as targets of this oxidative attack (2), and it is likely that injury involves terminal or irreversible oxidation of these reactive groups. Less severe oxidative damage occurs during reperfusion after shorter sublethal periods of ischemia and reperfusion (ischemic preconditioning), and this initiates a stress-adaptive signaling response (3,4).…”
mentioning
confidence: 99%
“…Protein thiols have been implicated as targets of this oxidative attack (2), and it is likely that injury involves terminal or irreversible oxidation of these reactive groups. Less severe oxidative damage occurs during reperfusion after shorter sublethal periods of ischemia and reperfusion (ischemic preconditioning), and this initiates a stress-adaptive signaling response (3,4).…”
mentioning
confidence: 99%
“…Experiments with pCMPSA also showed that at least some of the functionally important SH groups of Na ϩ -K ϩ -ATPase protein, which spans the cell membrane, are exposed to the extracellular environment. SH group location on the extracellular face of Na ϩ -K ϩ -ATPase has been demonstrated by recording the effect of selective application of pCMPSA on Na ϩ -K ϩ pump current in guinea pig ventricular myocytes (17), and this location also explains the rapid effect of pCMB (Fig. 1).…”
Section: Resultsmentioning
confidence: 89%
“…For example, superoxide generators reduce pump current in voltage-clamped rabbit ventricular myocytes by approximately 50% at all membrane potentials within 10 min [33]. Pump activity is also significantly reduced by intracellular application of thiolmodifying reagents, or depletion of cellular glutathione [34], [2] transmembrane region is in blue, the N-domain is in cyan, the P-domain is in yellow, and the A-domain is in purple.…”
Section: Oxidant Modification As a Reversible Regulator Of The Pumpmentioning
confidence: 99%